2022
DOI: 10.3390/nu14040846
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Cross-Sectional Study of the Consequences of the COVID-19 Lockdown on Women’s Health Behaviors in Spain

Abstract: Changes in health habits were observed during the COVID-19 pandemic. An unequal distribution of responsibilities may have generated unequal levels of stress in men and women, and, therefore, this may have led to different impacts on their health habits during lockdown. This study aimed to analyze the changes in eating habits, physical activity, sleep, and body weight in women, compared to men, because of lockdown. A comparative cross-sectional study was carried out. 2834 Spanish volunteers aged 19 to 76 comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Meanwhile, women’s overrepresentation among participants who gained weight during the pandemic reflects a globally and historically recognized problem concerning women’s over representation among the obese and severely obese [ 37 , 78 ]. It lends support to other studies that have raised alarm about women’s increased vulnerability to psychological distress during the pandemic [ 36 , 83 ], barriers to healthy eating including eating disorders, sleep disruptions, and fluctuations in weight [ 35 , 48 ], and risks to bodily health, including cardiovascular disease [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Meanwhile, women’s overrepresentation among participants who gained weight during the pandemic reflects a globally and historically recognized problem concerning women’s over representation among the obese and severely obese [ 37 , 78 ]. It lends support to other studies that have raised alarm about women’s increased vulnerability to psychological distress during the pandemic [ 36 , 83 ], barriers to healthy eating including eating disorders, sleep disruptions, and fluctuations in weight [ 35 , 48 ], and risks to bodily health, including cardiovascular disease [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 77%
“…Considerably more scholarly research has addressed gender differences in dietary concerns during the COVID-19 pandemic given sociocultural norms around household responsibilities and caregiving, and pre-existing gender-based vulnerabilities to stress, depression, and other diseases [ 35 37 ]. But the results of these studies of the pandemic’s impact on gender have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…3 This was sadly not true of many papers published on a similar theme. 13,14 The other Covid-19 papers in JHND all had a specific focus that made them more broadly useful. These included a focus on optimising nutrition care of patients hospitalised by Covid-19, 1 the impact of control measures on the nutritionally vulnerable 5 and controversies around vitamin D in population groups at heightened risk of Covid-19 related hospitalisation and death.…”
Section: Keeping Originality In Focusmentioning
confidence: 99%
“…Similar to many other journals, we did publish one study 3 that would fall into the reporting of the ‘obvious findings’ category, although it did include a sizeable population and estimated dietary intakes using robust measures 3 . This was sadly not true of many papers published on a similar theme 13,14 . The other Covid‐19 papers in JHND all had a specific focus that made them more broadly useful.…”
Section: Keeping Originality In Focusmentioning
confidence: 99%
“…Other studies have also reported increased smoking and alcohol use among men compared to women [ 20 , 22 , 25 27 ] during the pandemic. Furthermore, a study established more women than men reported increases in the amount of food intake and weight and poorer sleep quality and duration during lockdown periods [ 28 ]. Evidence has indicated that women are more vulnerable to experiencing pandemic-induced psychological distress [ 29 ] and for instance, may use alcohol to cope with stress as compared to men [ 30 ].…”
Section: Introductionmentioning
confidence: 99%